Sistem Pendukung Keputusan Pengurutan Berdasarkan Jenis Suara Anggota Baru Divisi Paduan Suara BIOS Menggunakan Metode Profile Matching (Studi Kasus: Logicio Choir FILKOM) - Dinul Wikramaditya Syah; Edi Santoso; Rizal Setya Perdana (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2017)
Faculty of Computer Science Choir's or commonly referred to with the Logicio Choir (LC) is a Division in the organization of Arts and Sports in an environment of Faculty of Computer Science called the BIOS (Badan Internal Olahraga dan Seni). The Division was used to accommodate FILKOM students and has talent in the field of the chorus. The participants emerged from the desire to improve the knowledge and skills of their music. To become a member of this choir performed need several stages of selection. The criteria assessed in the selection include the ability of auditory (hearing), the ability to read scores or not numbers, the ability to sing with good intonation, articulation and determination high and low tone of someone (ambitus tone). A large number of criteria in selecting a jury, at least as well as the results of the different criteria that each Member makes it difficult in reaching a decision. Profile Matching is one of the decision-making methods that is suitable for selecting the members objectively based on the criteria that are needed by the organization. Profile Matching is a decision-making mechanism to assume that there is an ideal level of predictor variables that must be owned by individuals, not the minimum level that must be passed. Assessment and calculation of the value gap based on 9 citeria: Ambitus, hearing 2 tone, hearing 3 tone, hearing 4 tone, hearing 5 tone, reading notes, reading block notes, singing mandatory song, singing free song. The result of the profile matching method implementation is it can be an efficient and effective solution in making a decision in the member admission. The system can be used to make a decision with the output of the system is in the form of urutan based on the final score from the highest score to the lowest with a total 61 test data with a percentage of validity 77.04%.